2020
DOI: 10.1111/jwas.12707
|View full text |Cite
|
Sign up to set email alerts
|

Larval growth, survival, and partial budget analysis related to replacing Artemia in larval culture of six freshwater ornamental fishes

Abstract: Cultured freshwater ornamental fish are primarily fed Artemia at early life stages. Development of alternative feeding strategies could decrease the Artemia reliance of ornamental producers, reduce labor costs, and improve industry resilience by diversifying larval feeding options. In this study, Corydoras aeneus, Synodontis eupterus, Synodontis nigriventris, Epalzeorhynchos bicolor, Pterophyllum scalare, and Trichogaster lalius larvae were offered one of four diets at first feeding: newly hatched Artemia or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Although MD1 and MD2 resulted in poor survival relative to Artemia, simple differences in physical characteristics of the MDs (i.e., observed differences in buoyancy) may have led to this result as opposed to any inadequacies related to digestibility. As was noted by Lipscomb et al (2020a), as well as by Cahu and Zambonino Infante (2001), species-specific feeding behaviors lend themselves to certain diets. In this case, MD3 was far more negatively buoyant than MD1 and MD2, which may have served to benefit Tiger Barb larvae.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although MD1 and MD2 resulted in poor survival relative to Artemia, simple differences in physical characteristics of the MDs (i.e., observed differences in buoyancy) may have led to this result as opposed to any inadequacies related to digestibility. As was noted by Lipscomb et al (2020a), as well as by Cahu and Zambonino Infante (2001), species-specific feeding behaviors lend themselves to certain diets. In this case, MD3 was far more negatively buoyant than MD1 and MD2, which may have served to benefit Tiger Barb larvae.…”
Section: Discussionmentioning
confidence: 67%
“…Although dormant Artemia cysts are easily stored and cultured for use relative to other live feeds, their collection is dependent on environmentally induced cyst blooms, which can result in market volatility and inflated costs (Cahu and Zambonino Infante 2001;Hamre et al 2013). These negative aspects of Artemia use as a live feed, coupled with biosecurity concerns inherent to introducing wild organisms into the rearing environment, have prompted numerous studies evaluating alternative first feeds (Lazo et al 2000;Wang et al 2005;Sautter et al 2007;Patterson et al 2016;Lipscomb et al 2020a).…”
mentioning
confidence: 99%
“…The buoyancy, sinking speed, and leaching losses of nutrients for all tested diets were not measured or compared during the feeding trial; however, the chemical attractiveness, physical characteristics, color, particle size, shape and manufacturing techniques, and nutrient leaching of diets in water could influence feed intake and nutrient utilization by pre‐ and post‐metamorphic stage fish (Lipscomb, Patterson, Wood, Watson, & DiMaggio, 2020; Teshima et al, 2000). Orihuela et al (2018) also found that the particle‐assisted rotational agglomeration (PARA) microdiets showed better performance for Fine flounder, Paralichthys adspersus as compared with Otohime diets because the manufacturing process produces less dense and smaller particle size PARA diets reducing sinking rates and increasing the probability of the larvae in detecting and ingesting the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Patra and Ghosh (2015) fed angelfish larvae with Artemia, rotifer, moina, and ceriodaphnia and reported the highest survival rate, 74.67%, in larvae fed with Artemia nauplii. Lipscomb et al (2020) fed angelfish larvae with Artemia and reported a survival rate of 62.7%. Briefly, the survival rates of the present study are quite acceptable for larval rearing in angelfish when the best survival rates of the literature are considered.…”
Section: Discussionmentioning
confidence: 99%